Indicators of mental disorders in UK Biobank—A comparison of approaches - Davis, Katrina A.S.; Cullen, Breda; Adams, Mark; Brailean, Anamaria; Breen, Gerome; Coleman, Jonathan R.I.; Dregan, Alexandru; Gaspar, Héléna A.; Hübel, Christopher; Lee, William; McIntosh, Andrew M.; Nolan, John; et al. (International journal of methods in psychiatric research, 2019)
Objectives For many research cohorts, it is not practical to provide a “gold‐standard” mental health diagnosis. It is therefore important for mental health research that potential alternative measures for ascertaining mental disorder status are understood. Methods Data from UK Biobank in those participants who had completed the online Mental Health Questionnaire (n = 157,363) were used to compare the classification of mental disorder by four methods: symptom‐based outcome (self‐complete based on diagnostic interviews), self‐reported diagnosis, hospital data linkage, and self‐report medication. Results Participants self‐reporting any psychiatric diagnosis had elevated risk of any symptom‐based outcome. Cohen's κ between self‐reported diagnosis and symptom‐based outcome was 0.46 for depression, 0.28 for bipolar affective disorder, and 0.24 for anxiety. There were small numbers of participants uniquely identified by hospital data linkage and medication. Conclusion Our results confirm that ascertainment of mental disorder diagnosis in large cohorts such as UK Biobank is complex. There may not be one method of classification that is right for all circumstances, but an informed and transparent use of outcome measure(s) to suit each research question will maximise the potential of UK Biobank and other resources for mental health research.